Growth Opportunity, Capital Structure And Profitability On Company Value - Nufyar, Ahmad; Mulyani, Erly (Journal of Multiperspectives on Accounting Literature, 2023)
Purpose: This study has a purpose to decide the impact of growth opportunity, capital structure, and Profitability on firm worth in metal area organizations recorded on the Indonesia Stock Exchange for the period 2017-2021. Methodology/approach: This examination is a kind of causal exploration that utilizes various straight relapse investigations to test the proposed speculation. The population in this study are metal organizations and so forth that are recorded on the Indonesia Stock Exchange in the 2017-2021 period, which are 17 organizations. The testing procedure utilized was purposive examining so the quantity of tests utilized in this review was 70 examples Findings: Wellsprings of information utilized in this study are information sources which are information accessible in the wake of being collected by different gatherings. The aftereffects of this study demonstrate that growth opportunities significantly affect firm worth, while capital structure and profitability significantly affect firm worth. Then growth opportunities, capital structure, and profitability at the same time affect firm worth Practical implications: For additional exploration, it is normal to look at different factors other than Growth Opportunity, Capital Structure, and Profitability and is supposed to build the example to be concentrated so the outcomes obtained are more influential. Originality/value: This research adds a profitability variable to differentiate it from previous research Keywords: Capital Structure; Firm Value; Growth Opportunities; Profitability.